Absolute Configurations of Melanoxadin, MR‐93A, Melanoxazal, and MR‐93B. Issue 3 (11th December 2014) - He, Tian‐Jun; Zhu, Shijun; Lu, Xiao‐Wei; Wu, Yikang; Li, Yan
Abstract: Fungal metabolites melanoxadin, MR‐93A, melanoxazal, and MR‐93B were synthesized with the key stereogenic centers derived from commercially available chiral building blocks. The optically active synthetic products with well‐defined absolute configurations provided authentic samples for the stereoisomers of these oxazole‐containing natural products and thus allowed for unambiguous assignments of their relative and absolute configurations. The large discrepancies in the optical rotations between the natural and the pure synthetic samples are discussed. Some errors in the previously reported NMR signal assignments are also corrected. Abstract : The title compounds were isolated from Trichoderma sp. in the mid‐1990s, and their planar structures were established by spectroscopic means. However, information on the configurations has been missing, unavoidably created lasting uncertainty about the molecular identity of these bioactive oxazoles, especially when some of the reported optical rotation data were incorrect. Here we address these stereochemistry questions.